Law as a means to an end : threat to the rule of law / Brian Z. Tamanaha. - Tamanaha, Brian Z. (Law in Context., 2006)
The contemporary US legal culture is marked by ubiquitous battles among various groups attempting to seize control of the law and wield it against others in pursuit of their particular agenda. This battle takes place in administrative, legislative, and judicial arenas at both the state and federal levels. This book identifies the underlying source of these battles in the spread of the instrumental view of law - the idea that law is purely a means to an end - in a context of sharp disagreement over the social good. It traces the rise of the instrumental view of law in the course of the past two centuries, then demonstrates the pervasiveness of this view of law and its implications within the contemporary legal culture, and ends by showing the various ways in which seeing law in purely instrumental terms threatens to corrode the rule of law.